PEMANFAATAN POTENSI DESA DALAM PEMBELAJARAN PAUD DI DESA KECEMEN KECAMATAN MANISRENGGO KABUPATEN KLATEN - Maharani (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
This study uses a descriptive qualitative approach with the aim of describing the utilization of local potential in Kecemen Village, Manisrenggo District, Klaten Regency. Kecemen Village has a wealth of diverse natural and artistic potential. This potential is utilized by early childhood education institutions in the Kecemen Village area as a learning resource or early childhood learning media. There are 3 early childhood education institutions, both formal and non-formal in Kecemen Village, namely Pertiwi Kecemen I Kindergarten, Pertiwi Kecemen II Kindergarten, and Barokah playgroup. The three institutions take advantage of local potential as a source of learning for their students, namely through outbound activities in the Karangmodjo field, sports at the Setja Manggala Sports Center, playing water in the Kali Tumpeng Dam, learning to dance Jathilan, etc. Preserving, maintaining and caring for the existing local potential is a shared responsibility. Thus, it is necessary to always maintain good relations and cooperation between the Mother of Early Childhood Education in the Village, Early Childhood Education Institutions, the Village Government, and the surrounding community to facilitate early childhood education activities in Kecemen Village, Manisrenggo District.